2022
DOI: 10.3390/ma15155158
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Surface Treatment Degree of Steel Sheets in the Bonding Process

Abstract: The aim of the paper is to determine the influence of the surface treatment on the adhesive properties of steel sheet surfaces and the strength of the adhesive joints of steel sheets. The paper also aims to assess the degree of steel sheets’ surface treatment in the bonding process. Due to the many methods of surface treatment and types of materials, the assessment of the surface treatment method is extremely important in adhesive processes. Two variants of the surface treatment were used: without a paint coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The paint fills micro-irregularities and, after hardening creates mechanical anchors, promoting its bond strength. Surface topography plays an important role in the study of surface properties of solids because roughness can affect wettability [ 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The paint fills micro-irregularities and, after hardening creates mechanical anchors, promoting its bond strength. Surface topography plays an important role in the study of surface properties of solids because roughness can affect wettability [ 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the focus is on the mechanical strength approach to the analysis of adhesive joints and the adhesives themselves, without touching on the chemical aspects in too much detail, which, in the longer term, may contribute interesting observations to the results of the paper. As described above, the final strength of structural adhesive joints has been shown to be relative to several factors, such as the state of preparation of the surfaces to be bonded [ 49 , 50 ], the type of adhesive used and its modifications [ 51 ], the curing conditions of the joint [ 52 ] and the operating conditions, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Surface pretreatment is one of the most important links in adhesive bonding. Rudawska et al [ 6 ] evaluated the effect of surface treatment on the bonding performance of steel plate surface and joint strength, and found that the surface of degreased steel plate has better wettability with both polar and apolar fluids. Gonzalez-Canche et al [ 7 ] characterized the surface treatment through wettability, morphology and chemical analysis, and found that the treatment of metal layers by a sodium hydroxide and nitric acid pickling process improved the degree of adhesion and tensile strength of fiber metal laminates.…”
Section: Introductionmentioning
confidence: 99%